2010
DOI: 10.4049/jimmunol.0902890
|View full text |Cite
|
Sign up to set email alerts
|

Intense Antiextracellular Adaptive Immune Response to Human Cytomegalovirus in Very Old Subjects with Impaired Health and Cognitive and Functional Status

Abstract: Human aging is characterized by expanded and altered adaptive immune responses to human CMV (HCMV). It is unclear whether this expansion has its origins in age-related homeostatic disturbances or viral reactivation, whether anti-CMV immune surveillance may still be effective, and what are the consequences of this expanded immune response for health and longevity. We conducted an observational cross-sectional study in groups of HCMV-seropositive subjects aged ≥65 y of variable health status to compare the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 58 publications
1
53
2
Order By: Relevance
“…In contrast, CD4-specific response against CMV was increased in our groups with worse functional capacity. In an analogous manner, Vescovini et al recently reported that groups of elderly individuals with cognitive impairment and poor functional capabilities had significantly higher anti-CMV IgG titers and higher CD4+ T cells specific for CMV, although they used different criteria to score their patients and their subjects (Vescovini et al 2010) and we have also analyzed a larger number of variables which have never been correlated before to functional status in elderly. The cell repertoire limitation and the high degree of differentiation caused by CMV infection could play a major role in the reduced anti-CD3 response of T cells in the elderly with worse functional status.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CD4-specific response against CMV was increased in our groups with worse functional capacity. In an analogous manner, Vescovini et al recently reported that groups of elderly individuals with cognitive impairment and poor functional capabilities had significantly higher anti-CMV IgG titers and higher CD4+ T cells specific for CMV, although they used different criteria to score their patients and their subjects (Vescovini et al 2010) and we have also analyzed a larger number of variables which have never been correlated before to functional status in elderly. The cell repertoire limitation and the high degree of differentiation caused by CMV infection could play a major role in the reduced anti-CD3 response of T cells in the elderly with worse functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have implicated CMV to be associated with an increased risk of all-cause mortality (37) and to cause detrimental changes to the immune response (27)(28)(29) in older people. The paradox with the association of CMV seropositivity with the loss of immune function in older people is that overt CMV disease as a result of reactivation or new infections is not observed; however, there is an increase in detectable virus in urine in older people (44).…”
Section: Discussionmentioning
confidence: 99%
“…These cells have also been associated with the loss of the cytokine secretion ability and a limited proliferation capacity (19,22,27). These previous studies have led to the hypothesis that enlarged dysfunctional HCMV-specific CD4 ϩ T cell populations accumulate with age and that these HCMV-induced changes may become detrimental to individuals (27)(28)(29). However, it is noteworthy that in other studies, HCMV-specific CD4 ϩ T cells have also been shown to produce a range of antiviral effector functions, including production of multiple antiviral cytokines, and to have cytolytic effector functions (30)(31)(32).…”
mentioning
confidence: 99%
“…Since chronic persistent immune activation negatively impacts HIV disease progression (18,21,24,25,37,58,70,75) and immune activation in response to CMV may be responsible for accelerated immunosenescence (1,23,33,49,55,63,73,77), CMV replication localized to the genital tract is likely a major factor in HIV disease progression. Alternatively, seminal CMV replication may be a proxy for increased CMV shedding in other tissues that were not sampled in this study.…”
Section: Figmentioning
confidence: 99%